2017
DOI: 10.1016/j.bone.2016.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Focal osteoporosis defects play a key role in hip fracture

Abstract: BackgroundHip fractures are mainly caused by accidental falls and trips, which magnify forces in well-defined areas of the proximal femur. Unfortunately, the same areas are at risk of rapid bone loss with ageing, since they are relatively stress-shielded during walking and sitting. Focal osteoporosis in those areas may contribute to fracture, and targeted 3D measurements might enhance hip fracture prediction. In the FEMCO case-control clinical study, Cortical Bone Mapping (CBM) was applied to clinical computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 51 publications
(84 reference statements)
0
77
0
Order By: Relevance
“…Furthermore, the SPM endocortical density results of Poole and colleagues from a recent acute hip fracture study involving UK and Czech subjects are actually quite in agreement with those presented here for Chinese women. In that study, the authors confirmed that focal osteoporosis was specific to fracture type by using SPM of cortical and endocortical density parameters associated with targeted biopsies for micro‐CT measures . Unfortunately, the femoral head was not included in our surface‐based SPM analyses, thus limiting our visual comparisons to the rest of the proximal femur.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Furthermore, the SPM endocortical density results of Poole and colleagues from a recent acute hip fracture study involving UK and Czech subjects are actually quite in agreement with those presented here for Chinese women. In that study, the authors confirmed that focal osteoporosis was specific to fracture type by using SPM of cortical and endocortical density parameters associated with targeted biopsies for micro‐CT measures . Unfortunately, the femoral head was not included in our surface‐based SPM analyses, thus limiting our visual comparisons to the rest of the proximal femur.…”
Section: Discussionmentioning
confidence: 80%
“…These statistical atlases provide an opportunity to visualize a physical parameter of interest, such as vBMD or Ct.Th, in relation to a variable of interest . For example, Li and colleagues and Carballido‐Gamio and colleagues applied VBM to identify regions in the proximal femur where vBMD was significantly associated with acute and incident hip fractures, respectively, whereas Poole and colleagues applied surface‐based SPM to identify regions where Ct.Th and cortical and endocortical trabecular density parameters were significantly associated with acute hip fractures . These four studies demonstrated biological relevance by showing significant bone differences between fracture cases and controls in regions commonly involved with hip fracture …”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…In contrast, there was a lack of any appreciable tissue adaptation in the superior femoral neck region. This region is clinically relevant as: (1) it is exposed to greatest stress/strain during impact from a fall onto the greater trochanter; (2) femoral neck fractures appear to initiate in the region during a sideways fall; (3) the region experiences greater bone loss during aging compared with the more preserved inferior femoral neck; and (4) deficits in the region are associated with incident femoral neck fracture …”
Section: Discussionmentioning
confidence: 99%